Reproductive biology and development of gill glands in the inseminating characid, Macropsobrycon uruguayanae Eigenmann, 1915 (Cheirodontinae: Compsurini) - Azevedo,Marco A. (2010)
The reproductive biology and development of the gill gland are described for Macropsobrycon uruguayanae, an inseminating characid species of the tribe Compsurini, subfamily Cheirodontinae. Between April 2001 and March 2002, 117 males and 143 females of this species were collected in the rio Ibicuí, Uruguay basin in the State of Rio Grande do Sul, Brazil. Reproductively active individuals were present during most months sampled, indicating lack of a well-defined seasonal reproductive period. Several maturing females were found to be inseminated before completing full maturation. Histological analyses demonstrated spermatozoa within the ovaries of females in different stages of gonadal maturation collected during most months. No immature females had inseminated ovaries. Standard length at first gonadal maturation was estimated to be 24 mm for both males and females. Mean absolute fecundity was 191.08 (± 48.83 SD) oocytes per female, one of the lowest among characids. Relative fecundity was 0.539 (± 0.069 SD) oocytes per mg weight of the female, a value similar to that found for the majority of species of Cheirodontinae. The presence of two cohorts of oocytes within ovaries of M. uruguayanae indicates synchronous development, with total spawning. The mean diameter of mature oocytes was 0.6711 (± 0.1252 SD) mm, smaller than that found for the majority of species of Characidae. Gill glands occurred in all mature males, as well as in males undergoing advanced maturation. In the latter case, fewer gill filaments comprised the glands. Gill glands were not observed in immature males, males undergoing the initial stages of maturation, or in any female. A given gill gland may comprise as many as 24 filaments of the lateral hemibranch of the first gill arch. Secondary lamellae within most of the gill gland are greatly reduced, with columnar cells being present between them. These columnar cells contain abundant vesicles, suggesting secretory activity. The morphology of the gill gland of M. uruguayanae resembles that found in the majority of characid species that possess this structure.